The influence of traditional water governance on maintenance and decision-making: A review of the Royal Bafokeng Administration within the jurisdiction of Rustenbrug Local Municipality, North West - Manuel, Vinolia Maricia (The IIE, 2021)
Researchers in the field of water resource management have argued the importance in recognising the inclusion of traditional water management structures in rural areas of South Africa. In light of water management and supply to rural communities, they argue that the failure to incorporate and acknowledge features of these traditional water management structures could result in the undermining of governments capacity to achieve specific objectives set out by the national water act. However, due to the newly recognised role of these traditional water management institutions, perspectives have not adequately addressed the influence that these traditional institutions have on water management. The focus of this study was to specifically determine the influence that traditional water governance has on maintenance and decision-making within the jurisdiction of the water services authority (Rustenburg Local Municipality) and how this can lead to improved water governance in rural areas. In order to achieve improved water governance, one needs to understand the relationship between traditional and local government water management institutions. The main research question was to determine the influence that traditional water governance has on decision-making and maintenance in water management. Without an understanding of how traditional water governance influences maintenance and decision-making, improved water management and supply will not be possible in rural areas. Therefore, the aim of the study was to review the current relationship between the Royal Bafokeng Administration and Rustenburg Local Municipality and how it influences the maintenance and decision-making on water management and supply to the rural areas within the jurisdiction on Rustenburg Local Municipality. The study was qualitative, with in-depth semi-structured interviews and documentary analysis used to determine the relationship between the two institutions. The research aimed to identify the most significant factors in achieving improved water governance in 6 water management through the in-depth interviews. 13 people from the Royal Bafokeng Administration and the Rustenburg Local Municipality took part in the interviews. The outcomes of the study revealed that there is a lack of communication between the institutions concerning decision-making and maintenance of the shared wards. It was also revealed that the institutions have been operating in silos despite having an MOU in place and therefore negatively affecting shared services in the shared wards. It was further that the influence of traditional water governance within the context of the case study of the Royal Bafokeng Administration and that of the Rustenburg has a strong influence on decision-making and maintenance within the shared wards as it affects water management negatively due to the lack of collaboration.
Keywords: Water management; Water governance; Local government; Maintenance; Decision-making